Arbuscular Mycorrhizal Symbiosis Modulates Antioxidant Response and Ion Distribution in Salt-Stressed Elaeagnus angustifolia Seedlings - Chang, Wei; Sui, Xin; Fan, Xiao-Xu; Jia, Ting-Ting; Song, Fu-Qiang (Frontiers in Microbiology, 2018)
Elaeagnus angustifolia L. is a drought-resistant species.Arbuscular mycorrhizal symbiosis is considered to be a bio-ameliorator of saline soils that can improve salinity tolerance in plants. The present study investigated the effects of inoculation with the arbuscular mycorrhizal fungus Rhizophagus irregularis on the biomass, antioxidant enzyme activities and root, stem and leaf ion accumulation of E. angustifolia seedlings grown during salt stress conditions. Salt-stressed mycorrhizal seedlings produced greater root, stem and leaf biomass than the uninoculated stressed seedlings. In addition, the seedlings colonized by R. irregularis showed notably higher activities of superoxide dismutase (SOD), catalase (CAT) and ascorbate peroxidase (APX) in the leaves of the mycorrhizal seedlings in response to salinity compared to those of the non-mycorrhizal seedlings. Mycorrhizal seedlings not only significantly increased their ability to acquire K+, Ca2+, and Mg2+ but also maintained higher K+:Na+ ratios in the leaves and lower Ca2+:Mg2+ ratios than non-mycorrhizal seedlings during salt stress. These results suggest that the salt tolerance of E. angustifolia seedlings could be enhanced by R. irregularis. The arbuscular mycorrhizal symbiosis could be a promising way to restore and utilize salt-alkaline land in northern China.